Latin-American challenges and opportunities in rheumatology - Rocha, Francisco Airton Castro (Arthritis Res Ther, 2017)
The importance of diseases to mankind is very similar worldwide. However, social and environmental issues, not to mention political and individual aspects, affect the prevalence and management of diseases and their outcomes. I present a brief and tentative comment to illustrate that the Latin-American rheumatology community, despite relevant gains in recent years, has some challenges to face in order to improve patient care in our region.